Healthcare services consumer’s behaviour and sustainable development - GÂRDAN (GEANGU), Iuliana Petronela; GÂRDAN, Daniel Adrian (Annals of Spiru Haret University. Economic Series, 2014)
Sustainable development has come into prominence in recent years as a concept that determines implications in all areas of human activity. Modern medical services are distinguished by a special position regarding application of the specific principles of sustainable development. This is because they are not only a necessary and useful tool to implement the concept of sustainable development at the scale of the entire human civilization but also an area of activity where sustainability is experiencing a complex application. In this context, health care consumer behaviour has also suffered substantial changes determined both by the technological evolution from the medical field and the large scale which phenomena such as social networks and communication technology has in the present. This article proposes a review of the evolution of the concept of sustainable development, its application in the medical field, with an emphasis on dental health services and final considerations on how consumer behaviour is influenced by the implementation, at the level of the medical organisations, of the principles of sustainable development.